Role of mitochondria ROS generation in ethanol-induced NLRP3 inflammasome activation and cell death in astroglial cells - Alfonso-Loeches, Silvia; Ureña-Peralta, Juan R.; Morillo-Bargues, Maria José; Oliver-De La Cruz, Jorge; Guerri, Consuelo (Frontiers in Cellular Neuroscience, 2014)
Toll-like receptors (TLRs) and Nod-like receptors (NLRs) are innate immunity sensors that provide an early/effective response to pathogenic or injury conditions. We have reported that ethanol-induced TLR4 activation triggers signaling inflammatory responses in glial cells, causing neuroinflammation and brain damage. However, it is uncertain if ethanol is able to activate NLRs /inflammasome in astroglial cells, which is the mechanism of activation, and whether there is crosstalk between both immune sensors in glial cells. Here we show that chronic ethanol treatment increases the co-localization of caspase-1 with GFAP+ cells, and up-regulates IL-1β and IL-18 in the frontal medial cortex in WT, but not in TLR4 knock-out mice. We further show that cultured cortical astrocytes expressed several inflammasomes (NLRP3, AIM2, NLRP1 and IPAF), although NLRP3 mRNA is the predominant form. Ethanol, as ATP and LPS treatments, up-regulates NLRP3 expression, and causes caspase-1 cleavage and the release of IL-1β and IL-18 in astrocytes supernatant. Ethanol-induced NLRP3/caspase-1 activation is mediated by mitochondrial (m) ROS generation because when using a specific mitochondria ROS scavenger, the mito-TEMPO (500 M) or NLRP3 blocking peptide (4g/ml) or a specific caspase-1 inhibitor, Z-YVAD-FMK (10 M), abrogates mROS release and reduces the up-regulation of IL-1β and IL-18 induced by ethanol or LPS or ATP. Confocal microscopy studies further confirm that ethanol, ATP or LPS promotes NLRP3/caspase-1 complex recruitment within the mitochondria to promote cell death by caspase-1-mediated pyroptosis, which accounts for ≈ 73 % of total cell death (≈22%) and the remaining (≈25%) die by caspase-3-dependent apoptosis. Suppression of the TLR4 function abrogates most ethanol effects on NLRP3 activation and reduces cell death. These findings suggest that NLRP3 participates, in ethanol-induced neuroinflammation and highlight the NLRP3/TLR4 crosstalk in ethanol-induced brain injury.